Transformation of principles of staff formation in social service organizations of Kazakhstan - Jazykbayeva, B.K. (Journal of Economic Research & Business Administration, 2016)
The purpose of the social service system is to maximize the satisfaction of citizens who are in need of special social services to improve their life expectancy and improve its quality. Based on these requirements, in today’s developed countries the provision of public services should be organized in a way to simulate the market economic conditions. Government organizations are endowed with the highest possible degree of economic independence and compete with the private and nonprofit sector for the client, i.e., seek to reduce costs and improve the quality of services. One of the manifestations of economic independence, close to market conditions, consists in the system of staffing position struc ture planning, established in social service organizations in the developed countries. The elaborated standards will be appropriate to the principles of staff valuation applied in the world practice.